2009
DOI: 10.1002/joc.1853
|View full text |Cite
|
Sign up to set email alerts
|

Applicatıon of detrended fluctuation analysis to temperature data from Turkey

Abstract: ABSTRACT:Temperature is a basic weather and climate element and has a major role in the prediction of climate change. In this study, by using detrended fluctuation analysis (DFA), scaling exponent of daily mean temperature, daily maximum temperature, daily minimum temperature and daily temperature differences are calculated for 52 stations in Turkey. Local changes of scaling exponents are examined and their relation to the geographical structure is discussed. It is shown that all of the calculated scaling expo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
14
0
2

Year Published

2015
2015
2019
2019

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 24 publications
(21 citation statements)
references
References 26 publications
2
14
0
2
Order By: Relevance
“…A great number of studies have applied DFA successfully to meteorological time series. More specifically, DFA has been used in the study of climate for temperature time series [17][18][19][20][21][22], relative humidity [23,24], precipitation amount [25], drought and flood indices [26], ozone data [27][28][29][30], incident flux of solar radiation [31], examining the variability of the atmosphere for a very wide temporal range [32], and the North Atlantic Oscillation [33], among others.…”
Section: Introductionmentioning
confidence: 99%
“…A great number of studies have applied DFA successfully to meteorological time series. More specifically, DFA has been used in the study of climate for temperature time series [17][18][19][20][21][22], relative humidity [23,24], precipitation amount [25], drought and flood indices [26], ozone data [27][28][29][30], incident flux of solar radiation [31], examining the variability of the atmosphere for a very wide temporal range [32], and the North Atlantic Oscillation [33], among others.…”
Section: Introductionmentioning
confidence: 99%
“…As early as 1951, Hurst () demonstrated that the annual run‐off record from the Nile River displayed a long‐term persistence (self‐similar), and he developed the “Hurst exponent” to characterize the long‐term persistence. Subsequently, long‐term persistence has been recognized in many time series, such as economic (Muchnik, Bunde, & Havlin, ), climatic (Orun & KoçAk, ), and water quality (Shi, Liu, Huang, Zhang, & Su, ) data sets. Calculation methods for the Hurst exponent include detrended fluctuation analysis (DFA) (Onderka et al, ), wavelet transforms (Simonsen, Hansen, & Nes, ), and rescaled range analysis (Nnaji, ).…”
Section: Introductionmentioning
confidence: 99%
“…As early as 1951, Hurst (1951) demonstrated that the annual run-off record from the Nile River displayed a long-term persistence (self-similar), and he developed the "Hurst exponent" to characterize the long-term persistence. Subsequently, longterm persistence has been recognized in many time series, such as economic (Muchnik, Bunde, & Havlin, 2009), climatic (Orun & KoçAk, 2009), and water quality (Shi, Liu, Huang, Zhang, & Su, 2010) data sets.…”
Section: Introductionmentioning
confidence: 99%
“…In the current literature, determination of long-term persistence is another important research area. In this area, autocorrelation function, fluctuation analysis (FA), de-trended fluctuation analysis (DFA), spectral analysis, Hurst method, wavelet method and fractal dimension are e96 F. M. KORKMAZ AND K. KOÇAK used frequently in order to determine the long-term persistence properties of a given variable (Govindan and Kantz, 2004;Kavasseri, 2004;Kavasseri and Nagarajan, 2005;Harrouni and Guessoum, 2009;Koçak, 2009;Orun and Koçak, 2009;Telesca et al, 2016).…”
Section: Introductionmentioning
confidence: 99%